1987
DOI: 10.1111/j.1558-5646.1987.tb02464.x
|View full text |Cite
|
Sign up to set email alerts
|

PARTHENOGENESIS IN THE TROPICAL GEKKONID LIZARD,NACTUS ARNOUXII(SAURIA: GEKKONIDAE)

Abstract: found only females in a series of 51 specimens ofN. arnouxii from American Samoa. Preliminary data (discussed below) suggest that these represent a unisexual species that reproduces parthenogenetically.In this paper, the geographic distribution of bisexual and parthenogenetic populations is estimated from the sex ratio of museum samples of N. arnouxii. This analysis is complemented by assays ofchromosomal and electrophoretic variation in freshly collected specimens from bisexual and parthenogenetic populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Equally, the term apomixis (apomictic thelytoky) is sometimes used when referring to animals [74] . Thelytoky Hexapoda Odonata Exceptional [34] and Ephemeroptera Very common [35] Deuterotoky Blattoptera Very common [11,36] Mantoptera Very common [11] Isoptera Very common [11] Plecoptera Rare [37] Orthoptera Very common [11] Embioptera Occurs in Oligotomidae [11] Phasmida Very common [11] Psocoptera Less than 4 % [38] Phthiraptera Bovicola sp (Mallophaga) [39] Hemiptera Common, universal in aphids [11,40] Thysanoptera Some species [41] Strepsiptera One possible example [42] Thelytoky and Hexapoda Coleoptera (beetles) 54 Curculionidae, 11 Chrysomelidae, rare in other families [11,40,43] Deuterotoky Hymenoptera Very common [11] Diptera Found in several families [11] Lepidoptera Several Psychidae exceptional elsewhere [40] Echinodermata Asteroidea and Stelleroidea Rare or absent [44] Vertebrata Pisces About eight species (Poeciliidae, Cyprinidae, Atherinidae and Cobitidae) [45] Amphibia About three Ambystoma [45] Reptilia About 36 lizards and two snakes [46][47][48][49][50][51][52][53][54][55] R: Reduced eggs; F: fertilisation of eggs; C: equivalent to clonality. * Except for certain automicts (see Figures 1-3).…”
mentioning
confidence: 99%
“…Equally, the term apomixis (apomictic thelytoky) is sometimes used when referring to animals [74] . Thelytoky Hexapoda Odonata Exceptional [34] and Ephemeroptera Very common [35] Deuterotoky Blattoptera Very common [11,36] Mantoptera Very common [11] Isoptera Very common [11] Plecoptera Rare [37] Orthoptera Very common [11] Embioptera Occurs in Oligotomidae [11] Phasmida Very common [11] Psocoptera Less than 4 % [38] Phthiraptera Bovicola sp (Mallophaga) [39] Hemiptera Common, universal in aphids [11,40] Thysanoptera Some species [41] Strepsiptera One possible example [42] Thelytoky and Hexapoda Coleoptera (beetles) 54 Curculionidae, 11 Chrysomelidae, rare in other families [11,40,43] Deuterotoky Hymenoptera Very common [11] Diptera Found in several families [11] Lepidoptera Several Psychidae exceptional elsewhere [40] Echinodermata Asteroidea and Stelleroidea Rare or absent [44] Vertebrata Pisces About eight species (Poeciliidae, Cyprinidae, Atherinidae and Cobitidae) [45] Amphibia About three Ambystoma [45] Reptilia About 36 lizards and two snakes [46][47][48][49][50][51][52][53][54][55] R: Reduced eggs; F: fertilisation of eggs; C: equivalent to clonality. * Except for certain automicts (see Figures 1-3).…”
mentioning
confidence: 99%
“…Genetic sampling is still too sparse to provide a satisfactory resolution to interrelationships among the New Guinea pelagicus group populations, although five studies to date have revealed some surprising indications of diversification. Moritz's (1987) study demonstrated that populations from Oceania were unisexual (pelagicus) and the Pacific Rim populations harbored at least three different bisexual populations, two of which occurred in Papua New Guinea. Subsequently, Donnellan and Moritz's (1995) electrophoretic data identified two major clades in the pelagicus group of bisexuals.…”
Section: Genetic Lineagesmentioning
confidence: 91%
“…This figure also indicated the presence of two "species" (karyotypes) in the Port Moresby area. Moritz (1987) expanded his analysis of multiple island samples of this taxon, and his results were the keystone study that identified the potential diversity of this presumed widespread species. The key aspects were (1) demonstration of the occurrence of allfemale populations broadly in the south central Pacific Islands,(2) the sympatry of uni-and bisexual populations in Vanuatu,and (3) karyotypic and allelic evidence for multiple differentiated bisexual populations in New Guinea and Australia.…”
Section: History Of Discoveries In Australo-pacific Nactusmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast to the high level of species diversity of lizards and snakes, there is only limited information about the time required to establish the postzygotic RIMs in most lineages of squamates. Most examples of viable F 1 hybrids of squamates come from unisexual species (e.g., Leiolepis [ 55 ]; Darevskia [ 56 ]; Aspidoscelis [ 57 ]; Lepidodactylus [ 58 ]; Hemidactylus [ 59 ]; Heteronotia [ 60 ]; Nactus [ 61 ]). In these cases, however, further reproduction of the hybrids that may be otherwise sterile is enabled by parthenogenesis and/or multiplication of the gene dosage (triploidy, tetraploidy).…”
Section: Introductionmentioning
confidence: 99%